Gaining Social Capital by Consumption and Indebtedness as a Tool of Conversion - Cetin, Beyzade Nadir (Istanbul Univ, 2018)
With a consumerist society, the term `commodity,' gained value through symbolic meanings, that were attached to a commodity itself. Signs, images, symbols and belonging identifiers that indicate a station are used for commoditization, which is defined as the transformation of an object or experience into a merchantable product' In a consumerist society, a commodity gains its meaning from symbolic and belonging values, whose meanings are beyond the commodity's intrinsic value. At this stage the essential advantage of the economic system's hegemony- mainly the manufacturers' - is that an object or experience, which can be a subject of a purchase and sale relation, is encumbered with unlimited and an infinite number of meanings. So, what is expected from the consumer is to attribute value to the commodity based on any of these meanings, and still buy the commodity. While the system is creating such a perception, it also provides various ways to eliminate the deficiencies that could possibly prevent consumption. Since it is accepted that in the context of a consumerist society, the whole order is based on consumption, the most significant point that an individual does not - cannot - consume is financial incapability. The system creates various debt and credit instruments such as credit cards, consumer credits, and advance accounts, in order to remove this incapability. In this study, the debt phenomenon is going to be evaluated within the perspective of social capital phenomenon. Indebtedness will also be analyzed as a conversion strategy for social capital, and the traces, which are thought that the hegemony of indebtedness has created, will be followed within the study.
Keywords: Social capital; indebtedness; conversion strategy; consumer society